A decade of hospital costs for firearm injuries in the United States by region, 2005–2015: government healthcare costs and firearm policies. Issue 1 (2nd May 2022) - Spitzer, Sarabeth A; Forrester, Joseph D; Tennakoon, Lakshika; Spain, David A; Weiser, Thomas G
Abstract : Background: Firearm injuries are a costly, national public health emergency, and government-sponsored programs frequently pay these hospital costs. Understanding regional differences in firearm injury burden may be useful for crafting appropriate policies, especially with widely varying state gun laws. Objective: To estimate the volume of, and hospital costs for, fatal and non-fatal firearm injuries from 2005 to 2015 for each region of the United States and analyze the proportionate cost by payer status. Methods: We used the Healthcare Cost and Utilization Project Nationwide Inpatient Sample to identify patients admitted for firearm-related injuries from 2005 to 2015. We converted hospitalization charges to costs, which were inflation-adjusted to 2015 dollars. We used survey weights to create regional estimates. We used the Brady Gun Law to determine significance between firearm restrictiveness and firearm hospitalizations by region. Results: There were a total of 317 479 firearm related admissions over the study period: 52 829 (16.66%), 66 671 (21.0%), 134 008 (42.2%), and 63 972 (20.2%) for the Northeast, Midwest, South, and West respectively, demonstrating high regional variability. In the Northeast, hospital costs were 1.98 billion (13.9% of total), of which 56.0% was covered by government payers; for the Midwest, costs were 1.53 billion (19.7% of total), 40.4% of which was covered by government payers; in the South costs were highest at 3.2 billion (41.4% of total), but government payers only covered 34.3%; and costs for the West were 1.94 billion (25.0% of total), with government programs covering 41.6% of the cost burden. Conclusions: Hospital admissions and costs for firearm injuries demonstrated wide variation by region, suggesting opportunities for financial savings. As government insurance programs cover 41.5% of costs, tax dollars heavily subsidize the financial burden of firearm injuries and cost recovery options for treating residents injured by firearms should be considered. Injury control strategies have not been well applied to this national public health crisis. Level of evidence: Level II, Economic and Value Based Evaluation